Hubungan Kecemasan pada Visit Pre-Anestesi dengan Tekanan Darah sebelum Tindakan Anestesi di Rumah Sakit Universitas Sumatera Utara - Christine Christine; Cut Meliza Zainumi; Tasrif Hamdi; Husnul Fuad Albar (Jurnal Kesehatan Andalas, 2021)
Preoperative anxiety is frequently correlated with anesthesia procedures, resulting in the anesthesiologist being the most suitable person to decrease the patient's anxiety through effective doctor–patient communication during pre–anesthesia visits. During anxiety, one of the body responses is the release of epinephrine to the blood vessel resulting in increased blood pressure. Objectives: To knew the correlation between pre-anesthesia visit anxiety and blood pressure before anesthesia procedure. Methods: This study used a cross-sectional design that was conducted at Universitas Sumatera Utara General Hospital from September until October 2019. The sample was collected by consecutive sampling techniques, which meet inclusion and exclusion criteria. This study used primary data then was analyzed using Fisher’s Exact Test. Results: From 67 patients going through elective surgery, there are 41 patients (61,2%) with mild anxiety, 17 patients (25,4%) with moderate anxiety, and nine people (13,4%) with severe anxiety. There is no significant correlation (p>0,05) between anxiety with sex, types of anesthesia, PS ASA and heart rate. There is a significant correlation (p<0,05) between anxiety with blood pressure and types of surgery. Conclusion: There is a correlation between anxiety during the pre-anesthesia visit with blood pressure before anesthesia procedures.Keywords:  anesthesia, anxiety, blood pressure, pre-anesthesia visit